Identification and characterization of cytosolic fructose-1, 6-bisphosphatase in Euglena gracilis. Issue 12 (2nd December 2015) - Ogawa, Takahisa; Kimura, Ayako; Sakuyama, Harumi; Tamoi, Masahiro; Ishikawa, Takahiro; Shigeoka, Shigeru
Abstract: Euglena gracilis has the ability to accumulate a storage polysaccharide, a β-1, 3-glucan known as paramylon, under aerobic conditions. Under anaerobic conditions, E. gracilis cells degrade paramylon and synthesize wax esters. Cytosolic fructose-1, 6-bisphosphatase (FBPase) appears to be a key enzyme in gluconeogenesis and position branch point of carbon partitioning between paramylon and wax ester biosynthesis. We herein identified and characterized cytosolic FBPase from E. gracilis . The K m and V max values of EgFBPaseIII were 16.5 ± 1.6 μM and 30.4 ± 7.2 μmol min −1  mg protein −1, respectively. The activity of EgFBPaseIII was not regulated by AMP or reversible redox modulation. No significant differences were observed in the production of paramylon in transiently suppressed EgFBPaseIII gene expression cells by RNAi (KD- EgFBPaseIII ); nevertheless, FBPase activity was markedly decreased in KD- EgFBPaseIII cells. On the other hand, the growth of KD- EgFBPaseIII cells was slightly higher than that of control cells. Graphical abstract: : EgFBPaseIII, a cytosolic FBPase, may play an important role in carbon partitioning between paramylon and wax ester biosynthesis in Euglena gracilis .